Primeros auxilios psicológicos: una estrategia para reforzar la salud mental de las comunidades en tiempos de pandemia - Alé M., Danissa; Quevedo L., Yamil (Revista de Psiquiatría Clínica, 2022)
Introduction: The coronavirus pandemic has caused significant levels of distress in the population. As it progresses, the mental health burden is likely to increase and the responsiveness of the Health Network will be overwhelmed. The implementation of Psychological First Aid appears as a response element of the community. This article will expose its definition, evidence and essential concepts for the application of them in the current context of pandemic. Methods: A literature review is carried out. Psychological first aid involves providing immediate support to people experiencing a recent and serious crisis. These can be provided by anyone trained, being a community tool with the power to reach a large number of individuals. Distance communication resources could be an alternative to achieve greater coverage when using this psychological support. Results: The evidence on the training, implementation and effectiveness of psychological first aid is limited. This lack of evidence does not prove the absence of a useful effect, but rather the need for future studies on the effectiveness of these early interventions. Conclusions: Psychological first aid has emerged as a low-cost and potentially effective strategy in the context of a pandemic, justifying basic training in them, in preparation for other disasters. This pandemic is an opportunity for research, although there are doubts regarding the application of psychological first aid by remote means.